Laser tuned field emission of the carbon nanotube arrays grown on an optical fiber - Wei, XianQi; Li, Xin; Liu, WeiHua; Wang, XiaoLi (Science China. Technological sciences, 2014)
Laser was coupled into an optical fiber, on which covered a layer of well-aligned carbon nanotubes（CNTs） serving as cathode, to tune the field emission of the cathode. CNT arrays as field emission cathode were synthesized by chemical vapor deposition（CVD） on a naked fiber core. When the laser was coupled into the fiber, the turn-on voltage（Vto at a current density of 1 mA cm^-2） decreased from 1.0 to 0.9 kV and the emission current density increased from 0.83 mA cm^-2（at a 1 kV bias voltage） to 3.04 mA cm^-2 on 40 μm diameter fiber. A photon absorption mechanism is attributed to the field emission improvement. The estimated effective work function of CNT arrays on the optical fiber decrease from 4.89 to 4.29 eV. The results show the possibility of constructing a waveguide type laser modulated field emission cathode.